Rancang Bangun Sistem Komunikasi Pengingat Tagihan pada Kios di Daerah Urban Berbasis Android - Hamzah Dwi Aryanto Arya; Moh. Abdullah Anshori; Aad Hariyadi (Jurnal Jaringan Telekomunikasi, 2022)
A kiosk / traditional minimarket is a small shop that generally sells goods like a modern minimarket. During this pandemic, it is recommended to pay for an item without contact (online) to break the chain of the Covid-19 virus. Therefore, an Android-based smartphone is very useful for making payments for an item online. Most people desire to have an item they want even though the price offered is sometimes quite expensive. However, some buyers want to get the goods as soon as possible and for payment to wait for a certain period according to their ability. This is detrimental to the kiosk owners because they do not get income from selling their goods. This reminder makes it easier for sellers to collect bills automatically without waiting for buyers to shop again at the same kiosk. Besides that, there is a limit for each buyer, which is useful for kiosk owners, so they do not lose money. This research needs to have a communication system that can make it easier for kiosk owners to collect bills from their customers without waiting for the customer to come again to shop at the same kiosk. In other words, the kiosk owner has certainty from the customer according to the agreed payment due date.